Atlas of endoscopic ultrasonography - Gress, Frank G.; Savides, Thomas J.; Casey, Brenna; Artifon, Everson L. A.; Ohio Library and Information Network (Hoboken, NJ : John Wiley & Sons, Inc., 2021)
"Atlas of Endoscopic Ultrasonography, Second Edition offers an outstanding visual guide to this very common diagnostic and therapeutic endoscopic tool. With contributions from noted experts in the field, the Atlas contains 400 high-quality color and black and white images obtained from real cases, each accompanied by detailed annotation to aid readers in their understanding of this popular technical procedure. In addition, there is a companion website featuring 50 video clips of real-life procedures in action, as well as the entire collection of images from within the book. Updated throughout to include the most recent advances in interventional Endoscopic Ultrasound (EUS) guided therapies . Contains a large collection of color images obtained from both diagnostic and therapeutic procedures, also available on the companion website image bank . Provides a highly integrated and accessible multimedia introduction to endoscopic ultrasonography . Includes a companion website offering insightful videos Written for gastroenterologists, students, residents, and radiologists, Atlas of Endoscopic Ultrasonography, Second Editionis an essential introduction to endoscopic ultrasonography"--
Front Matter -- Normal EUS Anatomy. Normal Human Anatomy / John C Deutsch -- Esophagus / James L Wise, John C Deutsch -- Normal Mediastinal Anatomy by EUS and EBUS / Juan Corral, Sebastian Fernandez-Bussy, Michael B Wallace -- Stomach / Joo Ha Hwang -- Bile Duct / Kapil Gupta -- EUS of the Normal Pancreas / Richard A Erickson, James T Sing -- Liver, Spleen, and Kidneys / Nalini M Guda, Marc F Catalano -- Anatomy of the Anorectum / Christoph F Dietrich -- Upper and Lower GI EUS. Esophageal Cancer / Armen Eskandari, Syed M Abbas Fehmi -- EUS for Achalasia / Michael Chang -- Malignant Mediastinal Lesions / M Babitha Reddy, David H Robbins, Mohamad A Eloubeidi -- Benign Mediastinal Lesions / M Babitha Reddy, David H Robbins, Mohamad A Eloubeidi -- Gastric Cancer / Douglas O Faigel, Sarah A Rodriguez -- Gastric and Esophageal Subepithelial Masses / Muhammad Tahir, Andrew J Bain -- Anorectal Neoplasia / Manoop S Bhutani, Everson LA Artifon -- Anal Sphincter Disease / Raymond S Tang, Thomas J Savides -- Endometriosis / Jose Celso Ardengh, Juan Pablo Roman Serrano, Samuel Galante Romanini, Juliana Silveira Lima Castro, Isabela Trindade Torres -- Vascular Anomalies and Abnormalities / John C Deutsch -- Pancreatico-biliary. Duodenal and Ampullary Neoplasia / Brenna Casey, Kumar Krishnan -- Biliary Tract Pathology / Brenna Casey, Kumar Krishnan -- Gallbladder Pathology / Sam Yoselevitz, Ann Marie Joyce -- Pancreatic Adenocarcinoma / Douglas G Adler -- Pancreatic Malignancy (Non-adenocarcinoma) / Larissa Fujii-Lau, Michael J Levy, Suresh T Chari -- Autoimmune Pancreatitis / Larissa Fujii-Lau, Michael J Levy, Suresh T Chari -- Pancreatic Cystic Lesions / William R Brugge -- Intraductal Papillary Mucinous Neoplasms / William R Brugge -- Chronic Pancreatitis / David G Forcione -- Liver Pathology / Indraneel Chakrabarty, Ann Marie Joyce -- How to Section. How to Interpret EUS-FNA Cytology / Cynthia Behling -- How to do Mediastinal FNA / Sammy Ho -- How to do Pancreatic Mass FNA / Yunseok Namn, Jonathan M Buscaglia -- How to do Pancreatic Cyst FNA / Ahmad Najdat Bazarbashi, Linda S Lee -- How to do Pancreatic Pseudocyst Drainage / Shyam Varadarajulu, Vinay Dhir -- How to do EUS-guided Pancreatic Cyst Chemoablation / Matthew T Moyer, John M DeWitt -- How to do Celiac Plexus Block / Sam M Serouya, Adam J Goodman -- How to Place Fiducials for Radiation Therapy / Antonio R Cheesman, Satish Nagula, Christopher J DiMaio -- How to Inject Chemotherapeutic Agents / V Raman Muthusamy, Kenneth J Chang -- How to do EUS-guided Pelvic Abscess Drainage / Shyam Varadarajulu, Sandeep Lakhtakia -- How to do Doppler Probe EUS for Bleeding / Richard CK Wong -- How to do Endoscopic Ultrasound-guided Portal Pressure Gradient Measurement / Rintaro Hashimoto, Kenneth J Chang -- How to do Endoscopic Ultrasound-guided Liver Biopsy / David L Diehl -- How to do EUS-guided Treatment of Gastric Varices / Dalton Marques Chaves, Filipe Tomishige Chaves -- How to do EUS-guided Arterial Embolization / Marc Barthet, Jean-Michel Gonzalez -- How to do EUS-guided Radiofrequency Ablation of Pancreatic Neuroendocrine Tumors / Marc Barthet, Mohamed Gasmi, Jean-Michel Gonzalez -- How to do EUS Pancreatic Duct Access and Drainage / Alberto Larghi, Mihai Rimba, Mauricio K Minata -- How to do EUS Gallbladder Drainage / Shannon Melissa Chan, Anthony Yuen Bun Teoh -- How to do an EUS-guided Gastrojejunostomy / Sohini Sameera, Michel Kahaleh -- How to do EUS Elastography / Julio Iglesias-Garcia, Jose Lariño-Noia, Daniel Iglesia-Garcia, J Enrique Dominguez-Munoz -- How to do Contrast-enhanced EUS / Yasunobu Yamashita, Masayuki Kitano -- How to do EUS-guided Ablation of Pancreatic Neurendocrine Tumors / Sabrina Gloria Giulia Testoni, Gemma Rossi, Livia Archibugi, Paolo Giorgio Arcidiacono -- How to do EUS-guided Needle Confocal Laser Endomicroscopy of Pancreatic Cysts / Prashant Bhenswala, Frank G Gress -- How to use ex vivo Models in Teaching Therapeutic Endoscopic Ultrasound / Spencer Cheng, Mauricio K Minata, Carlos K Furuya, Edson Ide -- How to do Endoscopic Necrosectomy / Wilson T Kwong -- How to Perform Pancreatic Mass Fine Needle Biopsy / Ahmad Najdat Bazarbashi, Linda S Lee -- How to Perform Endoscopic Ultrasound-directed Transgastric Endoscopic Retrograde Cholangiopancreatography (EDGE) / M Phillip Fejleh, Wilson T Kwong -- Index
Keywords: Endoscopic ultrasonography -- Atlases; Endoscopy, Digestive System; Digestive System Diseases -- diagnostic imaging; Digestive System -- diagnostic imaging; Ultrasonography; Electronic books; Atlas; Scientific atlases; Atlases